2021
DOI: 10.1093/clinchem/hvaa239
|View full text |Cite
|
Sign up to set email alerts
|

Towards an SI-Traceable Reference Measurement System for Seven Serum Apolipoproteins Using Bottom-Up Quantitative Proteomics: Conceptual Approach Enabled by Cross-Disciplinary/Cross-Sector Collaboration

Abstract: Current dyslipidemia management in patients with atherosclerotic cardiovascular disease (ASCVD) is based on traditional serum lipids. Yet, there is some indication from basic research that serum apolipoproteins A-I, (a), B, C-I, C-II, C-III, and E may give better pathophysiological insight into the root causes of dyslipidemia. To facilitate the future adoption of clinical serum apolipoprotein (apo) profiling for precision medicine, strategies for accurate testing should be developed in advance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…To obtain the same information, it would be required to perform PCR-based genotyping plus eight single apolipoprotein immunoassays. The advantages of such a multiplexed method as a candidate reference method for apolipoprotein quantitation and phenotyping using LC-MS/MS have also been recognized [28]. In our study, 98% agreement of apoE phenotype identified by LC-MS/MS and APOE genotyping was achieved which is comparable to previously published results [15].…”
Section: Discussionsupporting
confidence: 88%
“…To obtain the same information, it would be required to perform PCR-based genotyping plus eight single apolipoprotein immunoassays. The advantages of such a multiplexed method as a candidate reference method for apolipoprotein quantitation and phenotyping using LC-MS/MS have also been recognized [28]. In our study, 98% agreement of apoE phenotype identified by LC-MS/MS and APOE genotyping was achieved which is comparable to previously published results [15].…”
Section: Discussionsupporting
confidence: 88%
“…With mass spectrometry, detection of individual peptide components and comparison of molar ratios may improve risk prediction. Data are supplied on individual subfractions within apoB-containing particles and the extent of oxidation of phospholipids on apoB particles can be determined [ 192 , 272 , 273 ]. The method is antibody-independent and can be automated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, calibrators should be used that guarantee traceability to secondary and finally primary reference materials and behave in a common way. An example of a traceability chain to SI is depicted in Figure (source: ISO 17511:2020), recently discussed in more detail …”
Section: Achieving Long-term Robustness: Methods Development and Anal...mentioning
confidence: 99%
“…Traceability of apo­(a) was secondary through immunoassay measurement to SRM 2B . Currently, there are no reference materials available for apoC-I, C-II, C-III and E, but a working group of the International Federation for Clinical Chemistry (IFCC WG APO-MS, ) has developed a complete reference measurement system for global standardization of seven serum apolipoproteins . Long-term stability in our laboratory is exemplified for three apolipoproteins in two QC samples (Figure , with Levey-Jennings plots of apoA-I; (1.32 g/L) ± 0.07 (1SD 5.3%), apoB; (1.02 g/L) ± 0.04 (1SD 4.2%) and apo­(a); (102.0 nmol/L) ± 7.4 (1SD 7.3%)).…”
Section: Robust Performance Of Quantitative Bottom Up Proteomics: The...mentioning
confidence: 99%